Surat Penyerahan Tanah Sebagai Instrumen Jual Beli - Sinaga, Roulinta Yesvery (BAMETI Customary Law Review, 2024)
This study analyzes the position of land transfer letters as instruments for the sale and purchase of land conducted informally, particularly for uncertified land. This normative legal research focuses on the legal aspects of land transfer based on relevant laws, regulations, and customary law. The results indicate that although the sale and purchase of uncertified land are prone to disputes, this practice remains prevalent due to various reasons, including lack of procedural knowledge, avoidance of administrative costs, and the perceived simplicity of the process. Land transfer letters can function as the initial evidence of land possession and ownership by the buyer. Although not explicitly regulated by law, land transfer letters adhere to the principle of freedom of contract and are widely accepted in practice. These letters contain elements similar to sale and purchase deeds but with simpler formalities and witnesses. However, the existence of these letters has weaknesses, such as a lack of strong legal evidence and potential future conflicts. Therefore, this study suggests separate agreements regarding repurchase prices, timeframes, and voluntary sales submissions to avoid future disputes.